The Effect of Financial Knowledge and Financial Attitude on Financial Management Behavior Mediated with Locus of Control - Agustina, Nur Riska; Mardiana, Mardiana (MEC-J (Management and Economics Journal), 2020)
Financial management behavior becomes an issue that can’t be avoided at this moment, especially about a consumptive phenomenon. The consumptive phenomenon became a bad habit now. Therefore, the purpose of this study is to determine the influence of financial knowledge and financial attitude on financial management behavior and determine a locus of control mediates the indirect effect of financial expertise and financial perspective on financial management behavior. This study's population comprises the Economics Faculty at Universitas Islam Negeri Maulana Malik Ibrahim Malang. The sample in this study was taken by purposive sampling technique, which amounted to 270 respondents. The data analysis method used descriptive analysis, and data analysis used Partial Least Square (SmartPLS) 3 with the Sobel test mediation analysis. The research results show that financial knowledge and financial attitude have a positive and significant influence on financial management behavior. Other than that, financial expertise and financial attitude positively affect financial management behavior if mediated by a locus of control.